Judgment No. C-1008/2010 of the Constitutional Court of Colombia and its Foundation in the Lex Mercatoria - Figuera Vargas, Sorily Carolina (2019)
The Constitutional Court of Colombia, in its role as supreme interpreter of the Constitution of that country, declared article 1616 of the Civil Code as constitutional in Judgment C-1008 of 2010. Said article establishes the debtor’s liability for damages in contractual matter. The Court upholds its ruling using, among other arguments, article 74 of the Vienna Convention for the International Sale of Goods and article 7.4.4 of the UNIDROIT Principles of International Commercial Contracts, which means that the ruling was widely based on the lex mercatoria. In this article, the authors analyze the Court’s judgment and discuss about the uniform interpretation that the customs and practices of international commerce must be subjected to.